Differentiation and Integration of Research Facilities of Science and Engineering under Conditions of Their Sustainable Development - F. A. Romaniouk; I. I. Leonovich; A. I. Loyko (Наука и техника, 2005)
The paper considers main regularities of differentiation and integration of research at higher educational institutions. Peculiar features of integration process development in the activity of the BNTU research division are given in the paper. The paper contains indices of the BNTU research activity in 2004.